The Influence of Profitability and Liquidity on Corporate Social Responsibility Disclosure in Food and Beverage Sub-Sector Companies on the Indonesia Stock Exchange - Maudyenni Lintong; Inggriani Elim; Olivia Y. M. Sardjono (International Journal on Advanced Science, Education, and Religion, 2026)
This study aims to examine the effect of profitability and liquidity on Corporate Social Responsibility (CSR) disclosure in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2020-2024. The independent variable, profitability, is measured using the Return on Assets (ROA) ratio scale, which is the ratio between net profit and total assets of the company, and liquidity is measured using the Current Ratio (CR) ratio scale, which is the ratio between current assets and current liabilities. Meanwhile, the dependent variable, Corporate Social Responsibility (CSR) disclosure, is measured using the disclosure index based on the Global Reporting Initiative (GRI) using the disclosure method. This type of research is quantitative research using secondary data. The sampling technique used is non-probability sampling with a purposive sampling technique. The number of samples obtained was 30 companies over 5 years of observation, resulting in 150 observational data. The data analysis technique used was multiple linear regression using IBM SPSS software. The results of the study partially indicate that profitability and liquidity have a significant effect on CSR disclosure.